Allele mining in Brassicas screened for A. brassicae resistance - N, Poornima K; grover, Anita (The Indian Journal of Agricultural Sciences, 2020)
The non-expresser of pathogenesis related gene 1 (NPR1) has been an important component of the SA/JA mediated mechanism of defence in plants. Brassicas have been major group of crop plants that are facing huge yield losses due to biotic stresses especially through Alternaria blight caused by Alternaria brassicae. Among the plethora of proteins, the NPR1 protein coding gene has been emphasised upon and an attempt has been made to isolate NPR1 alleles from different brassica species. The sequences were annotated using FGENESH and a maximum-likelihood tree was constructed using NPR1 genes from cultivated and wild brassica and also NPR1 from other crops. Understanding the genome structure of NPR1 and tagging the resistance alleles to the genomic regions of NPR1 among all species of Brassica has been aimed at in the present study.